Fiscal Decentralization and Macroeconomic Performance in Pakistan - Ahmad, Saeed; Shah, SalyhaZulfiqar Ali; Mazhar, Fatima; Khan, Muhammad Raheel; Javaid, Muhammad Qasim (The journal of contemporary issues in business and government, 2022)
The study plans to analyze the part of fiscal decentralization and macroeconomic execution of Pakistan. The major goal of study was to investigate the effect of fiscal decentralization on macroeconomic performance and fiscal resource distribution system of Pakistan. The study employed secondary data comprising from 1972 to 2014 for examination. The distribution of resources among federal and provincial governments never remained simple and always recognized much complicated problem. This study categorized a number of problems in the system of fiscal division of resources of Pakistan. To examine the effect of fiscal decentralization on macroeconomic performance in Pakistan, the study evaluated a brief history of distribution of resources among the provinces. The commission reviewed the NFC awards since 1991 to improve the procedure of resource allotment among the provinces in Pakistan. Direct transfers of finances and grants have been increased for all the provinces due to these awards. The effectiveness, self-sufficiency and resource generation of Provinces get inducement to improve because of identical grants and in turn attain financial autonomy. The economic divergence of provinces can be removed through appropriate transfer of resources. The experimental results demonstrate that the fiscal decentralization prove to a valuable device to improve the economic stability, encourage the better allocation of resources and promote the economic development in Pakistan.